Methods of Assessment of the Welfare of Shelter Cats: A Review - Vojtkovská, Veronika; Voslářová, Eva; Večerek, Vladimír (Animals, 2020)
At any moment, there are millions of cats housed in foster care facilities for abandoned and stray animals for various reasons worldwide. Care, management and regulation among these facilities differ. Moreover, shelters can never substitute the full comfort of a good home for the animal, and the welfare of cats in shelters is a subject of discussion in many respects. Cats are animals sensitive to changes; for most of them, placement in a shelter is a stressful experience because of changes in routine, environment and the presence of other animals. Stress is reflected in changes in behaviour, causes fluctuations in physiological values and disrupts the immune system, which is a predisposition to the development or reactivation of disease. Evaluation of the presence and intensity of negative impacts is possible through the use of evaluation tools based on indicators that help set the environment and management of keeping so as to disrupt the quality of life as little as possible. Although a comprehensive and valid welfare tool that would evaluate animal-based and at the same time resource-based (or management-based) indicators of cats in shelters is not currently available, it is possible to use partial evaluation of individual welfare indicators to assess welfare. This review aims to provide the readers with an insight into current options of assessment of the welfare of cats in shelters with an emphasis on behavioural, physiological and health indicators with an application in both practical and scientific contexts.
Keywords: animal-based measures; cats; shelters; assessment; welfare